2021
DOI: 10.3390/nu13093134
|View full text |Cite
|
Sign up to set email alerts
|

Is Supplementation with Micronutrients Still Necessary during Pregnancy? A Review

Abstract: Introduction: Proper nutrition during pregnancy is important to prevent nutritional imbalances that interfere with pregnancy. Micronutrients play critical roles in embryogenesis, fetal growth, and maternal health, as energy, protein, vitamin, and mineral needs can increase during pregnancy. Increased needs can be met by increasing the intake of dietary micronutrients. Severe micronutrient deficiency or excess during pregnancy can have negative effects on fetal growth (intrauterine growth retardation, low birth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 193 publications
(279 reference statements)
1
29
0
3
Order By: Relevance
“…It is known that high doses of this vitamin can damage the fetal central nervous system and cause different congenital defects [ 17 , 36 , 39 ]. According to some experts, scientific data (based on studies in women with a singleton pregnancy) do not justify routine vitamin A supplementation, and the same applies to vitamins E, B1, B2 and K [ 86 ]. Without appropriate scientific studies, it is difficult to explicitly state that the same approach should be adopted for a twin pregnancy.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is known that high doses of this vitamin can damage the fetal central nervous system and cause different congenital defects [ 17 , 36 , 39 ]. According to some experts, scientific data (based on studies in women with a singleton pregnancy) do not justify routine vitamin A supplementation, and the same applies to vitamins E, B1, B2 and K [ 86 ]. Without appropriate scientific studies, it is difficult to explicitly state that the same approach should be adopted for a twin pregnancy.…”
Section: Resultsmentioning
confidence: 99%
“…The latest position statement of the US Preventive Services Task Force is very cautious and indicates there are too little data to estimate the benefits and risks of routine iron supplementation in pregnant women in order to prevent the adverse course of pregnancy and experts from this organization do not take a different stand with regard to multiple pregnancies [ 98 ]. The same approach is adopted by the American College of Obstetricians and Gynecologists, and just like the previous opinion, does not refer to iron supplementation in women pregnant with twins [ 86 , 99 ]. Routine iron supplementation for all women is also not recommended in Great Britain.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Folic acid deficiency around conception period is associated with neural tubal defects and other non-genetic congenital abnormalities (cleft lip and heart disease). It has been suggested that folic acid deficiency causes placental vasculopathy that contributes to spontaneous abortion, premature placenta abruption and preeclampsia [ 6 , 7 ]. Similarly, iron deficiency has been observed to decrease the weight of the newborn, increased premature delivery and other complications during delivery.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, iron deficiency has been observed to decrease the weight of the newborn, increased premature delivery and other complications during delivery. Iron is necessary for the placenta, uterine enlargement, red blood cell synthesis and fetal growth [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%